Combustion performance of hydrochars produced via citricacid-assisted hydrothermal carbonization of pomelo peel at various temperatures. Issue 1 (June 2021) - Ma, Ru; Fakudze, Sandile; Chen, Jianqiang
Abstract: The shortage of fossil energy has become a worldwide problem. China has a vast land and a dense population, and the consumption of energy is becoming huge day by day. Biomass as a renewable and eco-friendly energy source has attracted extensive attention from researchers. In this study, biomass fuel was prepared by hydrothermal carbonization (HTC) technology with pomelo peel as feedstock. The combustion performance of citric acid (CA) assisted hydrochar based on pomelo peel was investigated under different treatment temperatures. The results show that the sample of PPH220-CA can become a good biomass fuel with excellent C content of 71.2%, HHV value of 27.7MJ/kg and combustion adequacy of 3.04%, so it is possible to play a role in the energy field in the future as an alternative fuel for coal.